Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Ibu Hamil tentang Skrining Hipotiroid Bayi Baru Lahir di Wilayah Kerja Puskesmas Kawal - Mekar Zenni Radhia; Dewi Asmawati; Ika Rahmawati (Departement of Mathematics Education, 2023)
Congenital hypothyroidism, hereinafter abbreviated as HK, is a state of decreased or non-functioning thyroid gland that is acquired from birth onwards. This occurs due to anatomic abnormalities or metabolic disorders in the formation of thyroid hormone or iodine deficiency. The Bintan health office has also implemented the SHK program for newborns. In 2017 SHK had not been implemented at all in Bintan. Whereas in 2019 it was carried out but only 2.7% had just been implemented, namely out of 1353 babies only 49 babies were screened for hypothyroidism and the results of 49 who were screened were declared negative for hypothyroidism. The purpose of this study was to look at the knowledge and attitudes of pregnant women about screening hypothyroid. This study used pre-experimental research methods with pre- and post-test designs. With the aim of knowing the effect of health education on the knowledge and attitudes of pregnant women in carrying out hypothyroid screening in the work area of the Kawal Health Center, with a total population of 30 people and the entire population or total sampling was taken as a sample. The results showed that there were differences in knowledge and attitudes of mothers before and after being given health education. There is an effect of health education on mother's knowledge and attitudes where the p value is 0.003. The conclusion from this study is that there is an influence of mother's knowledge and attitude towards providing health education to pregnant women. hypothyroid.